Risk assessment of PCP lift system using a fishbone diagram and MICMAC method (2020)
Hydrocarbons demand by industrialized and developed nations and the oil prices conditions last few years; many companies have turned again to fields that were not previously considered attractive to produce, to identify them as an alternative to meet that demand. This research shows the identification of a condition, which should be taken into account to produce a mature field by progressive cavity pumping (PCP) artificial lift system, an evaluation with the MICMAC method and the identification of the key variables to achieve the development in this practice. The results make possible to identify highest influence elements, which can guide intervention strategies and form the basis to formulate guidelines and policies for the PCP implementation. The results allow us to conclude that pressures and mechanical designs in field wells should be the guidelines for optimum production, the market rate improvement, and the reservoir productive life.